INDEKS KOLEKSI MUSEUM RUMAH KELAHIRAN BAGINDO AZIZ CHAN - Utami Putri, Rifa; Hasfera, Dian (UIN Imam Bonjol Padang, 2022)
This research is motivated by the problem of the absence of a suitable search tool Present complete and detailed information about museum collections, which Making it difficult to find information about the home museum collectionThe birth of Bagindo Aziz Chan. The purpose of this research is to design And produce an information search tool in the form of a museum collection index Bagindo Aziz Chan's birth house that is valid, effective and practical so that you can Facilitate school children, students, students and the community. This research Is a development method. This research procedure consists of several Stages, namely conducting needs analysis, designing products, developing Products, and conduct trials. The test results of this product are declared valid Evidenced by the value of A from the Expert validator, the effectiveness of which is carried out on Large groups get a score of 80% of respondents stated